2020
DOI: 10.3390/rs12040709
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Long-Term Rainfall Trends and Variability in the Uttarakhand Himalaya Using Google Earth Engine

Abstract: This paper analyses the spatio-temporal trends and variability in annual, seasonal, and monthly rainfall with corresponding rainy days in Bhilangana river basin, Uttarakhand Himalaya, based on stations and two gridded products. Station-based monthly rainfall and rainy days data were obtained from the India Meteorological Department (IMD) for the period from 1983 to 2008 and applied, along with two daily rainfall gridded products to establish temporal changes and spatial associations in the study area. Due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 70 publications
(116 reference statements)
0
44
0
Order By: Relevance
“…Here, the precipitation dataset includes both rainfall and snow. Banerjee et al [59] analyzed the rainfall trend and variability in the Uttarakhand Himalaya from 1983 to 2008 and highlighted that CHIRPS has a greater degree of correspondence with observed rainfall than the Precipitation Estimation from Remotely Sensed Information using Artificial Neural Networks-Climate Data Record (PERSIANN-CDR). Several previous studies have analyzed the CHIRPS dataset and reported satisfactory results with other model simulated, satellite, and ground-based observations [60][61][62][63].…”
Section: Meteorological Datamentioning
confidence: 99%
“…Here, the precipitation dataset includes both rainfall and snow. Banerjee et al [59] analyzed the rainfall trend and variability in the Uttarakhand Himalaya from 1983 to 2008 and highlighted that CHIRPS has a greater degree of correspondence with observed rainfall than the Precipitation Estimation from Remotely Sensed Information using Artificial Neural Networks-Climate Data Record (PERSIANN-CDR). Several previous studies have analyzed the CHIRPS dataset and reported satisfactory results with other model simulated, satellite, and ground-based observations [60][61][62][63].…”
Section: Meteorological Datamentioning
confidence: 99%
“…Within GEE it is available as rainfall intensity (mm·hr −1 ) from 1999 to 2019. This dataset has been used in a large number of scientific studies carried out on GEE (Wang et al ., 2019; Zeng et al ., 2019; Banerjee et al ., 2020).…”
Section: Dataset and Methodsmentioning
confidence: 99%
“…The improved capacity of data science and infrastructure, e.g., cloud computing, Google Earth Engine (GEE) and big Earth data approaches, facilitates data sharing and the integration and modeling processes [87][88][89]. For example, the capacity and service from GEE open opportunities for explorations that benefit from decades of data acquisition from remote sensing [90][91][92][93][94][95][96].…”
Section: Remote Sensing Applications In Monitoring Of Protected Areasmentioning
confidence: 99%